Neuronal correlates of empathy : from rodent to human - Meyza, Ksenia Z.; Knapska, Ewelina (Academic Press, an imprint of Elsevier, 2018)
Neuronal Correlates of Empathy: From Rodent to Human explores the neurobiology behind emotional contagion, compassionate behaviors and the similarities in rodents and human and non-human primates. The book provides clear and accessible information that avoids anthropomorphisms, reviews the latest research from the literature, and is essential reading for neuroscientists and others studying behavior, emotion and empathy impairments, both in basic research and preclinical studies. Though empathy is still considered by many to be a uniquely human trait, growing evidence suggests that it is present in other species, and that rodents, non-human primates, and humans share similarities.